Ritual Sajen pada Penganut Sunda Wiwitan (Studi Komunikasi Budaya pada Penganut Sunda Wiwitan) - Melina, Melina; Azeharie, Suzy S. (Koneksi, 2020)
Sunda Wiwitan is a belief held by traditional Sundanese society or native Sundanese religion. Sundanese Wiwitan community is spread in West Java, one of which is Cigugur Village, Kuningan. In carrying out their religious activities, this group usually presents offerings. The rituals of offerings in Sunda Wiwitan have existed since the stone age. This ritual is a legacy from the ancestors handed down to the younger generation of Sunda Wiwitan through the communication process. This ritual is still carried out by the Sunda Wiwitan community until this day. The purpose of this research is to find out how the process of offering rituals on Sunda Wiwitan adherents and what are the preparations needed at the time of the ritual. Theories used in this research are communication theory, culture and ritual communication. The research method used was a descriptive qualitative research method with a phenomenological method. The data to be analyzed was obtained from the results of in-depth interviews with three speakers. The conclusion from this study is that ritual offerings are not a negative thing. But the offerings ritual is a ritual that presents the work of human beings to Sang Hyang Kersa or the Creator, creatures that appear or do not appear as expressions of gratitude and. This ritual is also a symbol that describes the relationship between humans and nature and humans with the Creator. Sunda Wiwitan merupakan sebuah aliran kepercayaan yang dianut oleh masyarakat tradisional Sunda atau agama Sunda asli. Masyarakat penganut Sunda Wiwitan tersebar di daerah Jawa Barat salah satunya adalah Desa Cigugur, Kuningan. Dalam menjalankan kegiatan agamanya kelompok ini biasa menyajikan sajen. Ritual sajen dalam Sunda Wiwitan sudah ada sejak zaman batu. Ritual ini merupakan warisan dari para leluhur yang diturunkan kepada generasi muda Sunda Wiwitan melalui proses komunikasi. Ritual ini masih dilaksanakan oleh masyarakat Sunda Wiwitan sampai saat ini. Tujuan dari penelitian ini adalah untuk mengetahui bagaimanakah proses ritual sajen pada penganut Sunda Wiwitan dan apa saja persiapan yang dibutuhkan pada saat ritual sajen dilakukan. Teori yang digunakan dalam penelitian ini adalah teori komunikasi, budaya dan komunikasi ritual. Metode penelitian yang digunakan adalah metode penelitian kualitatif deskriptif dengan metode fenomenologi. Data yang akan dianalisis diperoleh dari hasil wawancara mendalam dengan tiga orang narasumber. Kesimpulan dari penelitian ini adalah ritual sajen bukanlah sebagai suatu hal yang negatif. Tetapi ritual sajen merupakan ritual yang mempersembahkan hasil karya olah manusia kepada Sang Hyang Kersa atau Sang Pencipta, makhluk yang tampak maupun tidak tampak sebagai ucapan rasa syukur dan terima kasih. Ritual sajen juga merupakan simbol yang menggambarkan hubungan antara manusia dengan alam dan manusia dengan Sang Pencipta.